A bundled quality improvement program to standardize clinical blood pressure measurement in primary care. Issue 2 (21st December 2017) - Boonyasai, Romsai T.; Carson, Kathryn A.; Marsteller, Jill A.; Dietz, Katherine B.; Noronha, Gary J.; Hsu, Yea‐Jen; Flynn, Sarah J.; Charleston, Jeanne M.; Prokopowicz, Greg P.; Miller, Edgar R.; Cooper, Lisa A.
Abstract : We evaluated use of a program to improve blood pressure measurement at 6 primary care clinics over a 6‐month period. The program consisted of automated devices, clinical training, and support for systems change. Unannounced audits and electronic medical records provided evaluation data. Clinics used devices in 81.0% of encounters and used them as intended in 71.6% of encounters, but implementation fidelity varied. Intervention site systolic and diastolic blood pressure with terminal digit "0" decreased from 32.1% and 33.7% to 11.1% and 11.3%, respectively. Improvement occurred uniformly, regardless of sites' adherence to the measurement protocol. Providers rechecked blood pressure measurements less often post‐intervention (from 23.5% to 8.1% of visits overall). Providers at sites with high protocol adherence were less likely to recheck measurements than those at low adherence sites. Comparison sites exhibited no change in terminal digit preference or repeat measurements. This study demonstrates that clinics can apply a pragmatic intervention to improve blood pressure measurement. Additional refinement may improve implementation fidelity.